A linear programming model for power distribution with demand response and variable renewable energy. (1st November 2016) - Babonneau, Frédéric; Caramanis, Michael; Haurie, Alain
Highlights: Introduce a linear programming framework to model distributed generation, flexible loads and distributed energy resources. Provide a closed loop infrastructure and energy asset investment model. It optimizes system costs considering dynamic response to marginal costs of energy and reserve. Provide a illustration based on a scenario of strong variable energy penetration in an EU region. Abstract: A linear programming framework is proposed to model distribution network characteristics, and market clearing processes for flexible load and distributed energy resources providing reserve and reactive power compensation. One shows that the Nash equilibrium solution representing the interaction between utility and customers for demand response and distributed reserve transactions can be approximated by a linear program when the players (i.e. the customers) are numerous and tend to become infinitesimal. Then a linear program is shown to reveal the market prices, corresponding to the marginal cost for the utility. The goal in developing this model is to provide a new module for a regional long term model of development of smart energy systems. This module will then introduce in the modeling of energy transition, the new options and constraints that are provided by a penetration of renewables with the possibility of implementing distributed markets for demand response and system services permitted by the development of the cyber-physical layer. A case study of a potential smart urban distribution network in Europe is carried out and provides numerical results that illustrate the proposed framework.